Strategies for English Learning in Early Childhood Education - Nur Arifah Hanafiah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
This study aims to explore the urgency of English language skills in early childhood through English language learning strategies for early childhood education in the modern era. Focus is given to sensitive periods in child development that indicate optimal potential in language learning. The research identifies that various aspects of language should be introduced to children before age 8, when children's brain development reaches 80%. In order to maximize this period, learning strategies that motivate and boost the spirit of learning are proposed, especially in the context of English language teaching. The TPR (Total Physical Response) method, stories and songs are identified as effective and fun methods in teaching English to young children. By utilizing the everyday environment, both at school and at home, children can continue to enrich their understanding of language. Close collaboration between educators and parents is also highlighted as an important aspect in optimizing language learning. This research makes a valuable contribution in directing English language learning approaches that suit the characteristics and potential of early childhood.